Improvement of Operational Parameters for Precision Rolling Bearings by Cleaning Working Surfaces from Micro Pollution of Various Nature - Stelmakh A.; Kostyunik R.; Mikosianchyk O.; Kushchev A.; Ibraimov T.; Sydorenko O.; Zaichuk N.; Shymchuk S. (Журнал інженерних наук, 2023)
In manufacturing high-precision rolling bearings for aviation and urban machinery, the key tasks are to reduce the cost of production of such products, increase their efficiency and resource, and ensure their reuse after performing appropriate repair work. The results of many years of research show that these tasks can be successfully solved by cleaning the working surfaces of the parts of such precision tribonodes by non-contact pulse methods, particularly by using variable electromagnetic fields. The article describes the process of deep cleaning the working surfaces of parts of various high-precision ball bearings (from overall to miniature). During this cleaning, ferromagnetic and other impurities in the form of micro-, sub-micro- and nanoparticles were removed on a developed stand that can be used on an industrial scale. Further studies of cleaned bearings showed improved operational parameters such as reduced noise and vibration and the degree of magnetization. To achieve the specified results, appropriate cleaning methods were developed and tested.